033 Survey of mycotoxins in 2016 United States corn. (1st August 2017) - Hendel, E. G.; Gott, P. N.; Murugesan, G. R.; Jenkins, T.
Abstract: Mycotoxins, toxic secondary metabolites produced by common molds infecting grains and forages, can contaminate feed ingredients. The negative effects on livestock are dependent on the level, type, and duration of exposure as well as the age, species, and general health status of the animal. The current study's objective was to determine the occurrence and potential risk of mycotoxins to livestock species in the 2016 U.S. corn crop in comparison with the previous year. In total, 318 corn samples from 25 states (2015 harvest) and 387 corn samples from 26 states (2016 harvest) were submitted for analysis as part of the annual Biomin PROcheck Mycotoxin Survey. Samples were analyzed by liquid chromatography tandem mass spectrometry for the presence of mycotoxins from 6 major mycotoxin groups: type B trichothecenes including deoxynivalenol (DON), fumonisins (FUM), zearalenone (ZEN), aflatoxins (Afla), type A trichothecenes including T-2 toxin (T-2), and ochratoxin A (OTA). A summary of the results is provided in Table 033 . Individual toxin levels and co-occurrence from each year were compared using nonparametric tests (GraphPad Prism). In the 2016 sample pool, 90% of the corn samples had least one mycotoxin detected. Compared with 2015 corn, 2016 corn had higher contamination levels of DON and FUM ( P < 0.001). Additionally, co-occurrence of more than one mycotoxin increased from 2015 to 2016 (46 vs. 67%; P < 0.001). Toxins produced by Fusarium fungal species (DON, FUM, and ZEN) were frequently detected in combination; 21% of samples tested positive for all 3 toxins. Co-occurrence of mycotoxins can result in more severe detrimental impacts on animal health and performance. The high prevalence as well as large number of samples above the U.S. Food and Drug Administration–recommended level (42% of positive samples over 1, 000 ppb) positions DON as the greatest mycotoxin threat to livestock from the 2016 U.S. corn harvest. However, the high prevalence of co-occurrence suggests FUM and ZEN also present significant risks to animal health in 2016 corn. :